FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PELAYANAN PUBLIK PADA BIDANG PENDIDIKAN (Studi pada Kinerja Koordinator Wilayah Kecamatan Bidang Pendidikan dalam Pemenuhan Sarana dan Prasarana Sekolah Dasar Kecamatan Kutawaluya Kabupaten Karawang) - Sah Tedja Kusuma; Dadan Kurniansyah; Rachmat Ramdani (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research is motivated by the condition of elementary schools in Kutawaluya District, Karawang Regency, most of which have minimal facilities and infrastructure, seen from the damaged school room. This is very influential on teaching and learning activities (KBM), that the fulfillment of facilities and infrastructure is the responsibility of the Regional Coordinator for Education (Korwilcambidik) Kutawaluya as a government organization at the forefront of providing services to all primary school (SD) needs both in physical and administrative terms. The purpose of this study was to determine the performance of the Kutawaluya Regional Coordinator for Education (Korwilcambidik) in the provision of facilities and infrastructure in public elementary schools in Kutwaluya District, Karawang Regency. This study uses a descriptive method with a qualitative approach, by obtaining information from predetermined informants. This study uses the basis of analysis in measuring organizational performance from Soesilo (2014) which consists of aspects of organizational structure, management policies, human resources (HR), management information systems, and facilities and infrastructure. The results showed that the performance of the Korwilcambidik Kutawaluya organization in the service of facilities and infrastructure for public elementary schools in Kutawaluya District, Karawang Regency has not been optimally implemented. This can be seen from the lack of ability of the apparatus in carrying out work according to their main duties and functions, constraints on synchronization of accurate data regarding real needs related to facilities and infrastructure in 26 elementary schools (SD), not using the principle of the right man on the right pleace in organizations, In addition to the minimal mastery of information and communication technology due to the weak skills of the apparatus, this condition is exacerbated by the absence of operational vehicles, which results from the suboptimal performance of the Kutawaluya Korwilcambidik.